Comprehensive Substrate-Based Exploration of Probiotics From Undistilled Traditional Fermented Alcoholic Beverage ‘Lugri’ - Baliyan, Neha; Dindhoria, Kiran; Kumar, Aman; Thakur, Aman; Kumar, Rakshak (Frontiers in Microbiology, 2021)
Cereal-based traditional fermented beverages (TFBs) are prevalent among India’s ethnic community, and lugri is one such TFB popular among the tribal people of the Lahaul valley in North-Western Himalaya. Previous studies have reported that lugri harbors probiotics and contains amino acids and vitamins but comprehensive substrate-specific exploration of lugri for probiotic attributes is unexplored. The present study selected three substrate-based lugri (wheat, rice, and barley) to study their biochemical properties and explore potential probiotics. This study screened the best probiotic strains for antioxidant studies and the fermentative process. A biochemical analysis determined that rice-based lugri had a higher alcohol content, electric conductivity, crude protein, and lower pH than barley and wheat-based lugri. A total of 134 distinct morphotypes were screened, and 43 strains were selected based on their qualitatively superior acid and bile tolerance. Rice-based undistilled lugri harbored the most probiotics, with 22 out of 43 strains isolated. All 43 bacterial isolates exhibited properties like cell surface hydrophobicity, cell-auto aggregation, β-galactosidase, and exopolysaccharide production, supporting them as possible probiotics. Based on antibiotic susceptibility, hemolytic activity, and biofilm formation, all the bacterial strains were found to be non-pathogenic. Taxonomically, they ranged among eight distinct genera and 10 different species. Statistically, 12 isolates were found to be the most promising probiotic, and eight strains were isolated from rice-based undistilled lugri. Furthermore, the antioxidant activity of the promising isolates was tested, based on free-radical scavenging ability toward 2,2-diphenyl-1-picrylhydrazyl (4.39–16.41%) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (15.29–57.74%). The strain Lacticaseibacillus paracasei LUL:01 showed the best antioxidant activity and probiotic attributes, and hence was used for the production of fermented milk. The strain LUL:01 fermented the sterile milk within 18 h, and the viable count remained above the legal requirement of 6 log10 CFU/ml during 28 days storage at 4°C. The strain represents a suitable candidate for applying probiotic functional food formulation with several health benefits.